Deathbed choice by ASF-infected wild boar can help find carcasses - Morelle, Kevin; Jezek, Milos; Licoppe, Alain; Podgorski, Tomasz (Transboundary and emerging diseases, 2019)
African swine fever (ASF) is a fatal disease infectious to wild and domesticated suids. This disease entered the European Union in 2014 and recently reached western Europe, with the first cases observed in Belgium in September 2018. Carcasses of ASF-infected wild boar play an important role in the spread and persistence of the virus in the environment. Thus, rapidly finding and removing carcasses is a crucial measure for effective ASF control. Using distribution modelling, we investigated whether the fine-scale distribution of ASF-infected animals can be predicted and support wild boar carcass searches. Our results suggest that ASF-infected wild boar selected deathbeds in cool and moist habitats; thus, deathbed choice was mostly influenced by topographic and water-dependent covariates. Furthermore, we show that in the case of an epidemic, it is important to quickly collect a minimum of 75-100 carcasses with exact locations to build a well-performing and efficient carcass distribution model. The proposed model provides an indication of where carcasses are most likely to be found and can be used as a guide to strategically allocate resources.
Keywords: Animals; ekosystém; africký mor prasat; African Swine Fever; Ecosystem; Europe; zvířata; epidemie; Evropa; Evropská unie; virus afrického moru prasat; prasata; Swine; European Union; African Swine Fever Virus; Epidemics; Sus scrofa